Gut It Out: Laxative Abuse Mimicking Distal Renal Tubular Acidosis - Marius Sidler; Nilufar Mohebbi; Ewout J. Hoorn; Carsten A. Wagner (Karger Publishers, 2019)
Background: Distal renal tubular acidosis (dRTA) can be inherited or acquired. Case Presentation: Here, we describe the case of a 45-year-old female patient with non-anion gap metabolic acidosis, hypokalemia, and alkaline urine. She had a history of rheumatoid arthritis and kidney stones and failed to acidify urine upon the fludrocortisone and furosemide test. Therefore, the diagnosis of dRTA secondary to an autoimmune disease was made. A kidney biopsy was examined for markers of acid-secretory intercalated cells. Surprisingly, no obvious difference in the relative number of acid-secretory intercalated cells or in the distribution of major proteins involved in acid secretion was found. Furthermore, increasing doses of potassium citrate failed to correct the hypokalemia and acidosis. Since these findings were rather atypical for autoimmune dRTA, alternative causes of her hypokalemia and metabolic acidosis were sought. The patient was found to chronically consume laxatives, which can also cause kidney stones and may result in a false-positive urinary acidification test. Conclusion: Chronic laxative abuse may mimic dRTA and should therefore be considered in unexplained hypokalemia with non-anion gap metabolic acidosis.